Prevalence of Depression, Anxiety, and Stress Among Repatriated Indonesian Migrant Workers During the COVID-19 Pandemic - Harjana, Ngakan Putu Anom; Januraga, Pande Putu; Indrayathi, Putu Ayu; Gesesew, Hailay Abrha; Ward, Paul Russell (Frontiers in Public Health, 2021)
Introduction: Repatriated Indonesian migrant workers are vulnerable to developing serious mental health problems during the COVID-19 pandemic. This study aimed to assess the prevalence and associated factors of depression, anxiety, and stress among these populations during the COVID-19 pandemic. Methods: Guided by the health belief model, a cross-sectional study design was employed among 335 participants, and primary data were collected through an online survey. Measured using DASS-21, anxiety, depression, and stress were the dependent variables. We performed descriptive and inferential statistical analyses—logistic regression was used to predict independently associated variables. STATA was used to execute all data analyses. Results: The prevalence of depression, anxiety, and stress among repatriated Indonesian migrant workers were 10.15, 9.25, and 2.39%, respectively. The risk of anxiety and depression was low among those aged 21–30 years old, who had completed a university degree, were married, and had quarantined for 14 days. Conversely, the risk of anxiety and depression was high among those who had bad perceived health status, high perceived susceptibility, and negative stigma perception. Conclusion: The prevalence of depression, anxiety, and stress among repatriated Indonesian migrant workers was relatively low compared to the general population. The risk of anxiety and depression was low among young people, educated people, and those under effective quarantine, but the risk was high among those who had negative perceptions about their health, stigma, and susceptibility to the disease.